Profile of Body Mass Index and Physical Fitness of Santri of Al Yumna Qur'an Tahfizh Boarding School - Permadi, Asep Angga; Solahudin, Solahudin; Sonjaya, Azhar Ramadhana; Arifin, Z. (Indonesian Journal of Physical Education and Sport Science, 2023)
Purpose of study. This study aims to determine the description of body mass index and physical fitness of students of the Al Yumna Banyuresmi Garut Tahfizh Islamic Boarding School, Garut. Materials and methods. The method used was a quantitative descriptive survey, with the technique of the 2019 Department of Education of the Republic of the Philippines physical fitness instrument test. The variables in this study were BMI and Physical Fitness. The sampling technique used a random sampling technique of 57 people consisting of 27 men and 30 women, data collection techniques through the Philippine physical fitness test, BMI with anthropometric measurements, strength with push ups and basic plank, flexibility with zipper test and sit and reach , coordination with juggling test, agility using hexagon agility test, speed with 40 meter sprint test, strength with standing long jump, balance with stork balance test and reaction time speed with stick drop test. Results. The data processing method uses descriptive statistics using Microsoft Excel. For male students, there were 2 people (7.14%) in the underweight category, 5 people (18.52%) in the underweight category, 18 people (66.60%) in the normal category, 1 person (3.70%) in the overweight category, 1 person (3.70%) in the overweight category. As for females, there are 4 people (13.33%) with severe underweight, 2 people (6.66%) with mild underweight, 20 people (66.60%) with normal weight, 1 person (3.33%) with mild overweight and 3 people (10 %) with severe overweight. For men, the physical fitness category is very good as many as 17 people (62.96%), the good category is 10 people (37.03%) and for the category of very good, sufficient and less there are none (0%). Whereas for women the good category was 19 people (63.30%), the sufficient category was 11 people (36.50%). Conclusion. With the largest norm value of 5 for men having an average fitness value of 3.98 and 2.7 for women, the average for men and women is 3.34, this shows that the overall physical fitness of Tahfizh Qur'an Al Yumna Islamic Boarding School students is in the good category.